Gentle m-Calabi-Yau tilted algebras - Garcia Elsener, A. (Algebra and Discrete Mathematics, 2020)
We prove that all gentle 2-Calabi–Yau tilted algebras are Jacobian, moreover their bound quiver can be obtained via block decomposition. For two related families, the m-cluster-tilted algebras of type A and Ã , we prove that a module M is stable Cohen-Macaulay if and only if Ωᵐ⁺¹τM ≃ M.